2018
DOI: 10.20517/2394-4722.2017.58
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs as a liquid biopsy: a next-generation clinical biomarker for diagnosis of gastric cancer

Abstract: Accumulating evidence has suggested the potential clinical utility of novel body fluid biomarkers, or "liquid biopsy", using circulating tumor cells and cell-free nucleic acids from cancer patients. Noninvasive and reproducible, liquid biopsy could provide the basis for individualized therapeutic strategies by identifying genetic and epigenetic aberrations that are closely associated with cancer initiation and progression. MicroRNAs (miRNAs) are short noncoding RNAs that posttranscriptionally regulate gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…In conclusion, there are no currently known LB biomarkers that can be used for early and noninvasive distinction between particular UMT types. However, (1) there are recorded nucleic acid molecules released from both benign and malignant variants into the bloodstream [89,90,91,92]; (2) many molecular biomarkers reported in solid UMT have been noted in LB samples in different cancer types and these can be used for early diagnosis, prognosis, and therapeutic outcomes [93,94,95,96,97,98,99,100,101,102]; and (3) it is presumed that abnormal patterns in solid tumors should remain the same in CNA [35,36,37,38,39,67,73,74,75]. On the basis of these facts, we can state that it is theoretically possible, and highly likely in practice, to distinguish clinically between UMT types using the LB approach when appropriate molecular markers are employed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, there are no currently known LB biomarkers that can be used for early and noninvasive distinction between particular UMT types. However, (1) there are recorded nucleic acid molecules released from both benign and malignant variants into the bloodstream [89,90,91,92]; (2) many molecular biomarkers reported in solid UMT have been noted in LB samples in different cancer types and these can be used for early diagnosis, prognosis, and therapeutic outcomes [93,94,95,96,97,98,99,100,101,102]; and (3) it is presumed that abnormal patterns in solid tumors should remain the same in CNA [35,36,37,38,39,67,73,74,75]. On the basis of these facts, we can state that it is theoretically possible, and highly likely in practice, to distinguish clinically between UMT types using the LB approach when appropriate molecular markers are employed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many of the biomarkers of solid UMT described below have previously been reported in LB from patients with different cancer diseases and these provide the possibility of early diagnosis, prognosis, and therapeutic outcome. These include the identical microRNAs [93,94,95,96,97], methylation changes [95,98,99], mutational changes [100,101,102], and even similar chromosomal rearrangements [103,104,105,106]. We, therefore, suggest a way to identify LB biomarkers suitable for UMT differentiation by searching for abnormal patterns already established in solid UMT in LB samples.…”
Section: Known Abnormalities In Umtmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence suggests that miRNAs can be used as diagnostic biomarkers for several human malignancies including breast, lung, and gastric cancers (Bahrami et al, 2018;Komatsu, Kiuchi, Imamura, Ichikawa, & Otsuji, 2018;Yu, Guan, Cuk, Brenner, & Zhang, 2018). It has been reported that miRNAs can T A B L E 1 Oncogenic miRNAs regulate the pathogenesis of hepatocellular carcinoma through targeting the specific components of the PI3K/ AKT/mTOR signaling axis…”
Section: Mirna Panel As Biomarkers For Hcc Diagnosismentioning
confidence: 99%
“…MicroRNAs (miRNAs) are short noncoding RNAs that post-transcriptionally regulate gene expression. Komatsu et al [4] reviewed the recent biological and clinical research on the circulating miRNAs of gastric cancer and discussed the future perspectives.…”
mentioning
confidence: 99%